Designing the Intercultural Teaching Using “Dialogic Reading” Strategies for the English Students at Primary Schools - Sabilah, Fardini; Beratha, Sutjiati; Budiarsa, Made; Yadnya, Ida Bagus Putra (e-Journal of Linguistics; Vol 12 No 1 (2018): eJL-JanuaryDO - 10.24843/e-jl.v12i1.36221, 2018)
English in primary schools has been declared as an extra-curricular activity regulated by the 2013 Curriculum, otherwise it is no longer as a local content subject as stated in past curriculum. Due to this reason, English as an extra-curricular activity should not strictly followed teacher teaching guideline which has been written before by the local National education, however the teacher should concern more on creative teaching and learning process. On the other hand teachers at primary schools are to be ready to implement the suggested Curriculum and be well equipped with the skills to design the instructional materials and activities relevant to the Curriculum.   This current research aimed at designing Dialogic Reading guideline to teach Intercultural in the teaching of English in primary schools based on 2013 Curriculum. Intercultural instruction related to sensitivity to culture, intercultural communication skills, personal and group attitudes towards other cultures, as well as knowledge of other cultures whereas in primary schools this instruction introducing cultural aspects and values of both languages, L1 and L2 cultures. Meanwhile, Dialogic Reading is further elaborated into some communicative instructional activities through reading, in which students are to perform a dialogue upon reading. The subjects of this research was SDN Bunulrejo 2 Malang with two teachers as the models of teaching. This current research was conducted by means of Research and Development (R & D) design, employing the stages as follows: observation, planning and drafting Dialogic Reading instruction strategies  and guideline, trying out at schools, evaluation, FGD, expert validation, and finalizing the draft of Dialogic Reading guideline. After following those several stages, this R & D resulted Dialogic Reading Intercultural Instructional Strategies and for upper grades (4-6) students of Primary Schools. It is expected that those instructional strategies could be utilized by primary school teachers in wider scope and increase the students competence in English research.